POLYSEMICITY OF THE TERMS «DEMURRAGE» AND «DETENTION» APPLIED IN THE PRACTICE OF LINER AND TRAMP SHIPPING - Drozhzhyn, O. L.; Koskina, Y. O. (Science and Transport Progress, 2019)
Purpose. The presented study aims to systematize the definition of the terms «demurrage» and «detention», which are used in the theory and practice of maritime transportations, but are characterized by different meaningful definition when used in liner and tramp shipping, which requires the need for a comparative analysis. Methodology. For the stated comparative analysis, the applied information sources allowed to determine the specificity of the terms «demurrage» and «detention» both at the scientific level and at the level of practical implementation. Findings. The authors proved that despite their synonymous character, the terms «demurrage» and «detention» have fundamental differences when used in transportation contracts for the vessels of liner and tramp shipping. Taking into account the specific conditions of these organizational forms of shipping, the terms, the meaningful interpretation of which are the object of the study, have a different object of accrual, the procedure for substantiating the value of the corresponding rates and the procedure for calculating the total amount. Originality. The authors for the first time carried out a study in the context of two forms of organization of maritime transport (tramp and linear) and established the semantic features of the marine terms «demurrage» and «detention». Practical value. The commercial practice of transport companies, in particular shipping ones, is closely connected with technical, technological, organizational, legal, economic and even linguistic issues. The last aspect concerns the role of the accuracy of understanding of the terms by the parties to the transportation contracts concluded by shipping companies (liner and tramp shipping) with counterparties, since it is the responsibility of a material nature that follows from them. Clear interpretation of the terms is crucial to prevent possible disputes regarding the relevant payments. Uncertainty, which is currently present in scientific publications and literary sources of practical nature, leads to a free interpretation and substitution of the analyzed terms with each other without a clear distribution of the parties' responsibility in different forms of shipping.